An atlas of Hubble space telescope spectra and images of nearby spiral galaxies - Hughes, M; Alonso-Herrero, A; Axon, D; Scarlata, C; Atkinson, J; Batcheldor, D; Binney, J; Capetti, A; Carollo, C; Dressel, L; Gerssen, J; Macchetto, D; et al. (2003)
We have observed 54 nearby spiral galaxies with the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope to obtain optical long-slit spectra of nuclear gas disks and STIS optical (∼R band) images of the central 5″ × 5′ of the galaxies. These spectra are being used to determine the velocity field of nuclear disks and hence to detect the presence of central massive black holes. Here we present the spectra for the successful observations. Dust obscuration can be significant at optical wavelengths, and so we also combine the STIS images with archival Near-Infrared Camera and Multi-Object Spectrometer H-band images to produce color maps to investigate the morphology of gas and dust in the central regions. We find a great variety in the different morphologies, from smooth distributions to well-defined nuclear spirals and dust lanes.